CD52 Is a Prognostic Biomarker and Associated With Tumor Microenvironment in Breast Cancer - Wang, Jianxin; Zhang, Guangchen; Sui, Yang; Yang, Zhuowen; Chu, Yinzhu; Tang, Hailing; Guo, Binbin; Zhang, Cong; Wu, Changjun (Frontiers in Genetics, 2020)
Tumor microenvironment (TME) plays an essential role in the development and metastasis of breast cancer (BRCA). More studies are needed on the differences and functions of immune components and matrix components. In this study, we calculated the proportion of tumor-infiltrating immune cells (TICs) and the proportion of immune and matrix components of BRCA patients from the Cancer Genome Atlas (TCGA). We performed Cox regression analysis and constructed protein-protein interaction (PPI) network based on the differentially expressed genes (DEGs) and obtained the most crucial gene CD52. CD52 significantly up-regulated and affected the prognosis of BRCA patients. Gene set enrichment analysis (GSEA) suggested that the genes in the CD52 high-expression group were mainly enriched in immune-related pathways, while those in the CD52 low-expression group were mainly enriched in metabolic pathways. TICs analysis showed that there should be a positive correlation between CD52 expression and CD8 + T cells, activated memory CD4+ T cells, macrophage M1, and Gamma Delta T cells. It indicated that CD52 might be an essential factor in maintaining the immune-dominant position of TME. These results suggest that CD52 may be a potential biomarker for prognosis and provide a new therapeutic target for BRCA patients.